2021
DOI: 10.1007/s10067-021-05601-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on rheumatology practice in the UK—a pan-regional rheumatology survey

Abstract: The COVID-19 pandemic has disrupted healthcare services and rheumatology staff were redeployed to the frontline. The purpose of this survey was to evaluate the impact of the COVID-19 pandemic on the provision of rheumatology services as viewed by rheumatologists in the UK. Survey monkey questionnaire weblink was sent to 804 clinicians including consultant rheumatologists, speciality trainees, nurse specialists, and allied health professionals in 4 regions of the UK to evaluate personal effects of COVID-19 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 14 publications
3
21
0
1
Order By: Relevance
“…The findings reveal that every sixth rheumatologist has suffered from stress at least once in the past and the poor ratings of support services are a wakeup call. High levels of stress and mental health risks were also reported by other studies, although the results from different countries and surveys (which have applied different research aims and use different methods) may not be fully comparable [ 25 , 28 , 38 ]. Our material revealed that COVID-19 was an amplifier of stress.…”
Section: Discussion and Perspectivesmentioning
confidence: 83%
See 1 more Smart Citation
“…The findings reveal that every sixth rheumatologist has suffered from stress at least once in the past and the poor ratings of support services are a wakeup call. High levels of stress and mental health risks were also reported by other studies, although the results from different countries and surveys (which have applied different research aims and use different methods) may not be fully comparable [ 25 , 28 , 38 ]. Our material revealed that COVID-19 was an amplifier of stress.…”
Section: Discussion and Perspectivesmentioning
confidence: 83%
“…According to another US report, 32% of the surveyed rheumatologists felt burned out, of whom 29% stated that it began after the COVID-19 pandemic [ 25 ]. A survey in the United Kingdom revealed that “[t]wo-third of responders felt anxious about the ill-effects of COVID-19 on their health and wellbeing, and one third of them were redeployed” [ 28 ]. These findings are highly alarming, but evidence for German rheumatologists is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, clinicians may feel reluctant to make diagnoses/escalate immunosuppression without seeing patients in person, leading to many remote consultations converting to face-to-face reviews. This is particularly true for newly referred patients, with many rheumatology clinicians avoiding the use of remote appointments for new patients [ 3 ].…”
mentioning
confidence: 99%
“…10 Besides shielding measures and national lockdowns, redeployment of rheumatology providers as reported by different studies certainly played a role in these changes. 11 Outside of clinical care, rheumatologists have also played an active role in research even beyond that involving the treatment of patients with rheumatic disease; they have had important roles in the treatment of several complications of COVID-19. 12,13,14 The adoption of telemedicine in rheumatology has been quite heterogeneous, and similar to the results reported by Fernández-Ávila and colleagues, 5 some rheumatologists still have some hesitation about its use even past the pandemic.…”
mentioning
confidence: 99%
“…In a survey distributed among UK rheumatology healthcare professionals including 172 participants (49% consultants, 25% nurse specialists, and 12% specialty trainees), 90% used this modality in less than 1 in 4 consultations, despite the availability of video consultation for the majority of participants. 11 The limitations of providing care through telehealth, especially to new patients, are not trivial, but there is also much that can be accomplished in this model of care. Many would agree that for a known patient, the telehealth appointment can provide almost everything except the physical aspects of the patient-doctor interaction.…”
mentioning
confidence: 99%